Im just not seeing what im doing wrong to solve this. Can anyone take a look and let me know where I am going wrong with it?

4x + 1y = 16

-3(4x + 1y) = -3(16)

-12x + -3y = -48

2x + 3y = -24

-10x + 0y = -24

-10x = -24

-10/-10 = -24/-10

x = -2.4

4(-2.4) + 1y = 16

-9.6 + 1y = 16

(-9.6+9.6) + 1y = (16 + 9.6)

0 + 1y = 25.6

1y = 25.6

y=25.6

x=-2.4

4x + 1y = 16

4(-2.4) + 1(25.6) = 16

-9.6 + 25.6 = 16

2x + 3y = 24

2(-2.4) + 3(25.6) = 24

-4.8 + 76.8 = 72???

Works for one but not the other?